Effect of genotype, medium and light on in vitro plant proliferation of Vaccinium spp. Issue 4 (1st October 2016) - Scalzo, J; Donno, D; Miller, S; Ghezzi, M; Mellano, MG; Cerutti, AK; Beccaro, GL
ABSTRACT: The aim of this study was to investigate how growing conditions and media enhance blueberry proliferation. The effects of combinations of five Vaccinium spp. genotypes, two growing conditions and four proliferation media on plant growth were investigated. For shoot length and number of shoots, the factor responsible for the majority of the variance was the medium (13% and 22%, respectively). For callus size, the factor that caused the majority of the variation was genotype (22%). The medium that induced the longest shoot was ½MS0.3Z, while the medium that produced the highest number of nodes and the highest number of shoots was ½MS2Z. Genotypes 'Blue Bayou' and 'Centra Blue' produced an increased amount of callus over time, whereas the 'unreleased selection' genotype produced the least amount of callus. The genotype with the highest total plant fresh weight after 90 days was 'Blue Bayou' on WPM2Z medium in high light conditions.